2014
DOI: 10.2147/ndt.s69784
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine-induced seizures, electroencephalography abnormalities, and clinical responses in Japanese patients with schizophrenia

Abstract: PurposeWe describe electroencephalography (EEG) abnormalities and seizures associated with clozapine treatment in Japanese patients with schizophrenia and retrospectively compare EEG results and total Positive and Negative Syndrome Scale (PANSS [T]) scores before and after treatment.MethodsTwenty-six patients with treatment-resistant schizophrenia were enrolled in this study. EEG measurements were obtained prior to clozapine treatment and every 4 weeks thereafter. EEG measurements were also obtained at the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…In a study of 26 patients, EEG abnormalities were observed with average 305.0±131.7 mg dose in 10 patients. Clozapine dose was 200 mg/day in 3 of these 10 patients 4). Having seizures despite low dose clozapine suggests that there may be other risk factors than dose and titration rate for seizures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a study of 26 patients, EEG abnormalities were observed with average 305.0±131.7 mg dose in 10 patients. Clozapine dose was 200 mg/day in 3 of these 10 patients 4). Having seizures despite low dose clozapine suggests that there may be other risk factors than dose and titration rate for seizures.…”
Section: Discussionmentioning
confidence: 97%
“…It is thought that this situation causes high epileptogenicity of clozapine 7). Other possible mechanisms are anticholinergic efficacy of clozapine (H1, Ach-Mus receptor blockade) and its effects on other receptor types such as gamma-aminobutyric acid A, nicotinic acetylcholine, glutamate N-methyl-D-aspartate, serotonin 5-HT2A, and strychnine-sensitive glycine 4,12–16). Increasing seizure threshold of clozapine is dose-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a case of schizophrenia comorbid for tetralogy of Fallot, without chromosome 22q.11.2 deletion or duplication, was treated successfully with a combination of clozapine and antiepileptic drugs [28]. It is unknown how valproic acid is effective in clozapineinduced seizures without exacerbating psychological symptoms although it alters activity of clozapine by reducing its plasma level [29]. Lamotrigine and gabapentin are other options in clozapine-induced seizures; however, carbamazepine should be avoided as there is a risk for bone marrow suppression when used in combination with clozapine [9].…”
Section: Discussionmentioning
confidence: 99%
“…The seizure risk during CLZ treatment has been estimated at roughly 1–7.5% [ 27 , 28 , 29 ]. A VigiBase search indicated that the relative lethality associated with seizures from CLZ (5%: 308 fatal outcomes in 6231 cases) was approximately 2.5 times higher than that associated with agranulocytosis (2%: 550 fatal outcomes in 34,931 cases) [ 23 ].…”
Section: Adverse Drug Reactions Of Clzmentioning
confidence: 99%
“…During the titration and initiation of CLZ intake was a high risk period of CLZ-induced seizures, whereas during the maintenance of the CLZ dosage (even after several years of therapy), CLZ-induced seizures were not rare [ 27 , 38 ]. Additionally, a younger age also provided a risk of seizure [ 27 , 28 ].…”
Section: Adverse Drug Reactions Of Clzmentioning
confidence: 99%